1998
DOI: 10.1107/s0907444997012250
|View full text |Cite
|
Sign up to set email alerts
|

Human Carboxyhemoglobin at 2.2 Å Resolution: Structure and Solvent Comparisons of R-State, R2-State and T-State Hemoglobins

Abstract: Abstract1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 40 publications
4
31
0
Order By: Relevance
“…the distal His and the residue downstream one turn of the helix) impinge over the heme, too far away to make direct contact with it, but close enough to interact with the bound ligand. In Mb and the α chains of Hb (but not in the β) His E7 establishes a H-bond with bound oxygen [72,18], that has a bond angle of 120° to 160° in hemoproteins and in heme model compounds [73,18] and forces CO to a similar bent position [19,74,75], in spite of the fact that in heme model compounds CO adopts a linear geometry, normal to the porphyrin plane. Moreover His E7 increases the polarity of the heme pocket, again favouring O 2 over CO. Because of these reasons, His E7 is thought to be crucial to ligand discrimination, and it has been suggested that in its absence poisoning from endogenously produced CO would have lethal consequences.…”
Section: Control Of Oxygen Affinity In Hemo-globin and Myoglobinmentioning
confidence: 95%
“…the distal His and the residue downstream one turn of the helix) impinge over the heme, too far away to make direct contact with it, but close enough to interact with the bound ligand. In Mb and the α chains of Hb (but not in the β) His E7 establishes a H-bond with bound oxygen [72,18], that has a bond angle of 120° to 160° in hemoproteins and in heme model compounds [73,18] and forces CO to a similar bent position [19,74,75], in spite of the fact that in heme model compounds CO adopts a linear geometry, normal to the porphyrin plane. Moreover His E7 increases the polarity of the heme pocket, again favouring O 2 over CO. Because of these reasons, His E7 is thought to be crucial to ligand discrimination, and it has been suggested that in its absence poisoning from endogenously produced CO would have lethal consequences.…”
Section: Control Of Oxygen Affinity In Hemo-globin and Myoglobinmentioning
confidence: 95%
“…However, dynamic light-scattering characterization of Hb solutions prepared following procedures identical with those used here showed a single species of a size between 5 nm and 6 nm, 66 compatible with the 5.5 nm known for hemoglobin. 67,68 The high limit of the detection range of these determinations is above 1 mm. In view of the high sensitivity of light-scattering to larger species (e.g.…”
Section: Homogeneous Nucleation or Nucleation On A Substratementioning
confidence: 99%
“…19 A similar angle was found in COHb refined to 2.2 ) using human Hb, which transpired to be a mutant at the surface. 20 Spectroscopic studies have not supported the idea of a bent geometry, and strongly suggest the ligand pushes the distal residues aside to adopt its preferred conformation. One difficulty with the crystallographic refinements is that the ligand oxygen atom is largely unconstrained by its one chemical bond, and in the absence of very high resolution data the model must be restrained carefully using prior information.…”
Section: Introductionmentioning
confidence: 97%